Improving subacute management of post concussion symptoms: a pilot study of the Melbourne Paediatric Concussion Scale parent report - Gavin A Davis; Vanessa C Rausa; Franz E Babl; Katie Davies; Michael Takagi; Alison Crichton; Audrey McKinlay; Nicholas Anderson; Stephen JC Hearps; Cathriona Clarke; Remy Pugh; Kevin Dunne; et al. (Concussion)
Aim: To pilot a modification of the Post Concussion Symptom Inventory, the Melbourne Paediatric Concussion Scale (MPCS) and examine its clinical utility. Materials & methods: A total of 40 families of concussed children, aged 8–18 years, were recruited from the emergency department. Parent responses to the MPCS in the emergency department and 2-weeks post injury determined child symptomatic status. Association between MPCS symptom endorsement and symptomatic group status was examined. Results: All additional MPCS items were endorsed by at least 25% of the parents of symptomatic children at 2 weeks. MPCS items were classified into nine symptom domains, with most falling in mood, neurological, autonomic and vestibular domains. Conclusion: The additional items and domain classifications in the MPCS have the potential to improve subacute diagnostic precision, monitoring of clinical recovery and identification of appropriate interventions post pediatric concussion.